2021
DOI: 10.5946/ce.2020.194
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Endoscopic Ultrasound-Guided Biliary Drainage in Patients Undergoing Antithrombotic Therapy

Abstract: Background/Aims: The Japan Gastroenterological Endoscopy Society (JGES) has published guidelines for gastroenterological endoscopy in patients undergoing antithrombotic treatment. These guidelines classify endoscopic ultrasound-guided biliary drainage (EUS-BD) as a high-risk procedure. Nevertheless, the bleeding risk of EUS-BD in patients undergoing antithrombotic therapy is uncertain. Therefore, this study aimed to assess the bleeding risk in patients undergoing antithrombotic therapy. Methods: This single-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Therefore, we need to strengthen the treatment for acute coronary syndrome. Oral anticoagulants can reduce the risk of stroke and systemic embolism [ 29 ]. The effects of the two cannot be replaced by each other, but the combination of these two kinds of drugs increases the risk of bleeding, so how to find the balance of antithrombotic therapy in these patients is very important, and the risk of bleeding and thrombus needs to be fully assessed to maximize the benefit of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we need to strengthen the treatment for acute coronary syndrome. Oral anticoagulants can reduce the risk of stroke and systemic embolism [ 29 ]. The effects of the two cannot be replaced by each other, but the combination of these two kinds of drugs increases the risk of bleeding, so how to find the balance of antithrombotic therapy in these patients is very important, and the risk of bleeding and thrombus needs to be fully assessed to maximize the benefit of patients.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported an association of the use of cautery dilation with bleeding in EUS-BD. [ 27 ] It is noteworthy that none of the present patients required cautery dilation. Another study that compared cautery and mechanical dilation found no significant difference in terms of technical success rates: procedure-related bleeding developed in 6 (18%) patients with cautery dilation and in none during mechanical dilation ( P = 0.04).…”
Section: Discussionmentioning
confidence: 80%
“… 65 , 74 , 79 - 81 , 84 , 85 , 88 , 93 , 94 , 96 , 100 Some studies have advocated for continuing warfarin therapy before and after therapeutic procedures. 59 , 62 , 82 , 83 , 86 , 87 , 89 , 90 , 92 , 95 , 97 - 99 However, most of these studies were conducted in Japan, and their retrospective nature hampered changes in previous statements. 59 , 82 , 83 , 86 , 89 , 90 , 92 , 95 , 97 , 98 Considering that temporary interruption of anticoagulation therapy during procedures was associated with a significantly higher risk of thromboembolic events 53 and continuing antithrombotic therapy was associated with a significantly higher risk of procedure-related bleeding, 91 we still need to stratify the patients’ thromboembolic risk, and heparin bridging therapy is recommended for only patients with a high thromboembolic risk.…”
Section: Recommendations For the Management Of Antithrombotic Agentsmentioning
confidence: 99%